2023
DOI: 10.3389/fpsyg.2023.1200819
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on body image disturbances during pregnancy and postpartum: the role of cognitive reappraisal

Abstract: BackgroundDuring pregnancy, body size rapidly modifies over a relatively short period. Literature emphasizes the need to identify the factors that influence body image during peripartum as the extent of women’s adaptation to these changes has significant repercussions on both mother’s and newborn’s health. Emotion regulation strategies (i.e., expressive suppression and cognitive reappraisal) were linked to body image in the general and clinical population, but no studies were conducted in the peripartum. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
1
3
0
Order By: Relevance
“…17 Moreover, the opposite behavior could lead to an increase in cognitive and behavioral changes, such as body-checking, particularly after being preoccupied with one's body, 34 both among pregnant women and those in the postpartum phase. 32 According to the current study, self-compassion was found to negatively predict bodily behaviors among both groups in current study. However, factors showed varying results; for example, experiential avoidance and thought suppression were found to predict body-checking among pregnant women.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…17 Moreover, the opposite behavior could lead to an increase in cognitive and behavioral changes, such as body-checking, particularly after being preoccupied with one's body, 34 both among pregnant women and those in the postpartum phase. 32 According to the current study, self-compassion was found to negatively predict bodily behaviors among both groups in current study. However, factors showed varying results; for example, experiential avoidance and thought suppression were found to predict body-checking among pregnant women.…”
Section: Discussionsupporting
confidence: 48%
“…24 These intricacies are usually shaped by the social standards of beauty and also depend how they take their women versus mother role and an incongruence between these two is a cause of greater distress among these women 22 that may prevail postpartum. 25,32 Findings related to body checking outcomes and low self-compassion also suggests the role of self-stigma in bridging the link between them. 32 Our study showed that women who had lower levels of selfcompassion tended to engage in more body checking behaviors when they suppressed their thoughts during pregnancy and postpartum (especially the latter group as evident by group comparison).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations